The neuroprotective effects of isoquercitrin purified from apple pomace by high-speed countercurrent chromatography in the MPTP acute mouse model of Parkinson's disease. Issue 13 (28th May 2021) - Liu, Cong; Wang, Wenjuan; Li, Hao; Liu, Jiangang; Zhang, Peng; Cheng, Yong; Qin, Xiaoyan; Hu, Yang; Wei, Yun
Abstract : Isoquercitrin was isolated from apple pomace by HSCCC and proved to have neuroprotective effects on Parkinson's mice induced by MPTP. Abstract : Parkinson's disease is the second most common neurodegenerative disease. Researchers have shown that oxidative stress and apoptosis play an important role in the Parkinson's disease process. Isoquercitrin (quercetin-3- O -β-d -glucopyranoside) is a natural flavonol compound and one of the main active ingredients of agricultural waste apple pomace. Increasing evidence indicates that this compound possesses anti-oxidation, anti-aging, and anti-inflammation properties. In this study, isoquercitrin was purified from apple pomace by high-speed countercurrent chromatography and its neuroprotective effect on Parkinson's disease was investigated in MPTP-induced acute mouse models. It was found that isoquercitrin ameliorated the animal behaviors against MPTP-induced neurotoxicity, mitigated the loss of dopamine neurons induced by MPTP, increased tyrosine hydroxylase and dopamine transporter expression, reduced the pro-apoptotic signaling molecule bax expression and inhibited MPTP-triggered oxidative stress. Our results demonstrated that isoquercitrin has protective effects on the MPTP subacute model mouse, which might be partially mediated through the actions of anti-oxidation and anti-apoptosis. Isoquercitrin might be a new promising protective drug for the improvement of Parkinson's disease.